Myths and misconceptions about intelligence: A study of 35 myths. (October 2021) - Furnham, Adrian; Horne, George
Abstract: This study is concerned with the extent to which people believe in, and endorse, various myths about intelligence and intelligence testing. It examined the prevalence of myths about intelligence as set out in a recent book (Warne, 2020). Participants (N = 275) completed a questionnaire in which they rated the extent to which they thought various statements/facts about intelligence were essentially true or false. In all, eighteen of these myths were rated as true (definitely or partly), two as definitely false and six probably false by the majority of the participants. There were no significant demographic or personality correlates of the total correct score (determined by rating the myth as false). The discussion considers why, in this important area of psychology, myths, misconceptions and ignorance seem so difficult to dispel. Limitations of this, and similar, studies are noted, and implications are discussed. Highlights: Participants (N = 275) completed a questionnaire about 35 intelligence myths. 18 myths were rated as true (definitely or partly), two as definitely false and six a probably false. There were no significant demographic or personality correlates of the total correct score. The paper considers why myths, misconceptions and ignorance seem so difficult to dispel.